Preparation method and application of ultrathin composite polymer solid electrolyte suitable for low-temperature work

By encapsulating the lithium salt solution in an ultra-thin porous polymer film to form a composite polymer solid electrolyte, the problems of polymer electrolyte thickness and low temperature performance are solved, and high ionic conductivity in a wide temperature range are achieved. Solid-state lithium battery application in low temperature environment.

CN119170879APending Publication Date: 2024-12-20YANGTZE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411181970.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The polymer solid electrolyte has too thick thickness, poor mechanical strength, and poor low-temperature ion conductivity, resulting in poor performance of solid lithium batteries in low-temperature environments, limiting their promotion and application.

Method used

An ultra-thin porous polymer film is used as a skeleton to encapsulate the fast ion conduction medium, and the film is filled with lithium salt solution through dip coating to form a composite polymer solid electrolyte, improving mechanical properties and improving low-temperature ion conductivity.

Benefits of technology

Achieve high ionic conductivity in a wide temperature range, ensure the safety performance and energy density of solid-state batteries, and maintain normal charging and discharge and stable cycle under low temperature conditions (such as 0℃ or -10℃), significantly improving the battery's Applicability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170879A_ABST
    Figure CN119170879A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of a new energy material solid electrolyte and a solid-state battery, and particularly relates to a preparation method and application of an ultrathin composite polymer solid electrolyte suitable for working at low temperature. And drying to obtain the composite polymer solid electrolyte with excellent comprehensive performance. The preparation method specifically comprises the following steps: preparing a mixed solution of a polymer, a lithium salt and a solvent according to a certain proportion, soaking an ultrathin polymer film in the mixed solution for a certain time, repeatedly coating, and drying to obtain the target composite polymer solid electrolyte. The composite polymer solid electrolyte prepared by the invention has ultra-thin thickness, excellent mechanical performance and electrochemical stability, in addition, the electrochemical performance of the composite polymer solid electrolyte under a low-temperature condition is particularly excellent, the composite polymer solid electrolyte has the potential to be used as a solid electrolyte for a lithium ion battery working under a special condition, and the simple preparation method is more beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and in particular relates to a preparation method and application of an ultra-thin composite polymer solid electrolyte suitable for low-temperature operation. Background Art

[0002] With the replacement of electronic products and new energy vehicles, solid-state lithium batteries with high energy density and high safety are ushering in a new era. In recent years, there has been much attention paid to the cycle life and safety of solid-state batteries at home and abroad. However, the thickness of solid electrolytes, electrolyte / electrode interface, and low-temperature ion conductivity of solid-state batteries have become bottlenecks in their promotion and application. Among them, polymer solid electrolytes have the advantages of light weight, good flexibility, and easy preparation. In addition, it also has the advantages of flexible shape and size, and can also achieve higher energy density to meet practical application needs.

[0003] However, current polymer solid electrolytes still face problems such as low ionic conductivity, poor electrochemical stability, poor low-temperature performance and weak mechanical properties. Summary of the invention

[0004] In order to solve the technical problems existing in the above-mentioned prior art, such as the excessive thickness of the polymer solid electrolyte, the presence of pores due to solvent volatilization, which cannot effectively resist the growth of lithium dendrites, the poor mechanical strength and inability to be self-supporting, and the poor low-temperature ion conductivity, the present invention introduces an ultra-thin porous polymer film as the skeleton of the polymer solid electrolyte, thereby improving the mechanical properties of the composite polymer electrolyte while greatly reducing its thickness. In addition, an ion conductive medium with fast ion conduction capability is encapsulated inside the ultra-thin porous polymer film to achieve high ion conductivity of the composite polymer solid electrolyte in a wide temperature range, so that the solid-state battery assembled therefrom can achieve higher energy density while ensuring safety performance. In addition, its excellent low-temperature ion conduction performance can better guarantee its applicability in special working environments.

[0005] In order to achieve the above object, the present invention provides a method for preparing an ultra-thin composite polymer solid electrolyte suitable for low temperature operation, comprising the following steps:

[0006] (1) dissolving a lithium salt in a certain volume of an organic solvent M, controlling the temperature, and continuously stirring for a certain period of time to obtain a uniform solution A;

[0007] (2) placing the solution A and the polymer P in step (1) in an organic solvent N in a certain ratio, controlling the temperature to a certain level, and continuously stirring for a certain period of time to obtain a uniform solution B;

[0008] (3) filling the solution B in step (2) into the interior of an ultra-thin porous polymer membrane (preferably with a thickness of 5 to 25 μm) by a dip coating method, and then drying the membrane at a certain temperature for a period of time to obtain a target product, a composite polymer solid electrolyte;

[0009] The organic solvent M is selected from one or more of toluene, xylene, cyclohexanone, N-methylpyrrolidone, ethylene glycol, N,N-dimethylformamide, N,N-dimethylacetamide, methyl acetate, ethyl acetate, ether, methanol, and benzyl alcohol;

[0010] The organic solvent N is selected from one or more of tetrahydrofuran, butyl acetate, ethanol, propanol, isopropanol, n-butanol, isobutanol, acetone, methyl isobutyl ketone, methyl butyl ketone, dimethyl sulfoxide, and acetonitrile;

[0011] Furthermore, the organic solvent M and the organic solvent N are different organic solvents.

[0012] Preferably, the ultra-thin porous polymer membrane in step (3) is a commercial porous polymer membrane commonly available on the market or is homemade;

[0013] More preferably, the method for preparing the ultra-thin porous polymer membrane in step (3) is as follows:

[0014] The polymer Q is dissolved in a certain volume of organic solvent L, the temperature is controlled, and stirring is continued for a certain period of time to obtain a uniform solution C, and then the solution C is made into an ultra-thin porous polymer film by coating method, phase inversion method or electrospinning method;

[0015] Preferably, the lithium salt described in step (1) is selected from one or more of lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonic acid)imide (LiN(CF3SO2)2), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluorooxalatophosphate (LiPF4(C2O4)), perfluoroalkyl lithium phosphate (LiPF3(C2F5)3), and lithium bis(oxalatoborate) (LiBOB).

[0016] Preferably, the mass ratio of the lithium salt to the organic solvent M is (0.01-5):1, preferably (0.6-1.5):1.

[0017] Preferably, the stirring temperature in step (1) is 20-100° C., and the stirring time is 1-12 h, more preferably stirring at 30-50° C. for 4-6 h.

[0018] Preferably, the polymer P described in step (2) is selected from one or more of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer, carboxymethyl cellulose, polyethylene glycol methyl ether acrylate, polyvinyl alcohol, polyvinyl alcohol ether, polystyrene, polytrimethylene carbonate, polyethylene carbonate, polyvinylene carbonate, polypropylene carbonate, polycyanoacrylate, and polypentaerythritol tetraacrylate.

[0019] Preferably, the mass ratio of the polymer P, the solution A and the organic solvent N is (0.01-5):1:(5-50), more preferably 1:1:(15-20).

[0020] Preferably, the stirring temperature in step (2) is 20-80°C, and the stirring time is 1-12 hours, more preferably stirring at 40-50°C for 5-6 hours.

[0021] Preferably, the polymer Q is selected from one or more of polymethyl methacrylate, polytrifluoroethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyurethane, and polytetrafluoroethylene.

[0022] Preferably, the organic solvent L is selected from one or more of tetrahydrofuran, methyl acetate, ethyl acetate, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, benzyl alcohol, ethylene glycol, and N-methylpyrrolidone, and is different from the organic solvent N.

[0023] Preferably, the commercial porous polymer membrane is selected from one of polyethylene, polypropylene, polyurethane, polytetrafluoroethylene, polystyrene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer.

[0024] Preferably, the drying time in step (3) is 0.01 to 10 h, and the drying temperature is 20 to 100° C., more preferably, drying at 40 to 50° C. for 24 to 36 h.

[0025] The present invention also provides the use of the composite polymer solid electrolyte obtained by the preparation method in a solid lithium secondary battery.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The present invention uses a simple dip-coating method to in-situ encapsulate a polymer electrolyte that conducts lithium ions quickly inside an ultra-thin porous polymer membrane, thereby obtaining an ultra-thin composite polymer solid electrolyte with excellent mechanical properties.

[0028] (2) The composite polymer solid electrolyte material prepared by the present invention has an ultra-thin thickness, and still has good mechanical properties, good flexibility and electrochemical stability at an ultra-thin thickness, and can maintain excellent electrochemical properties while ensuring certain safety performance. In addition, the solid-state lithium metal battery assembled therein has unexpected low-temperature performance, and can charge and discharge normally under working conditions of 0°C or even -10°C, and can maintain a high discharge specific capacity and stable charge and discharge cycle. In addition, since it contains only a negligible amount of organic solvent, its safety performance as an electrolyte for lithium-ion batteries is greatly guaranteed.

[0029] (3) The composite polymer solid electrolyte provided by the present invention is not a simple combination of a lithium salt electrolyte and a polymer support, but a high-speed lithium-conducting complex medium is bound inside the support through the action of the polymer, and micropores are avoided during the drying process of the electrolyte by selecting different organic solvents, thereby achieving a dense composite polymer solid electrolyte, which greatly reduces the thickness of the polymer solid electrolyte and greatly improves its mechanical properties. In addition, it not only improves the low-temperature performance of the composite polymer solid electrolyte, but also makes it have excellent interface properties, while improving the transmission performance of lithium ions in the electrolyte and the electrolyte / electrode interface, it can effectively resist the growth of lithium dendrites, and achieve stable circulation of the solid-state battery assembled therein. In addition, the method for preparing the composite polymer solid electrolyte provided by the present invention is simple and easy to implement, and is suitable for large-scale industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a cross-sectional SEM image of the composite solid polymer electrolyte obtained in Example 1;

[0031] Figure 2 is the stress-strain curve of the composite solid polymer electrolyte obtained in Example 1;

[0032] Figure 3 This is a cycle performance diagram of an all-solid-state battery assembled with a composite solid polymer electrolyte obtained in Example 1 and LiFeO4 and a metal lithium electrode at room temperature at 0.5C;

[0033] Figure 4 This is a cycle performance diagram of an all-solid-state battery assembled with a composite solid polymer electrolyte obtained in Example 1 and LiFeO4 and a metal lithium electrode at 0°C and 0.1C;

[0034] Figure 5 It is a charge and discharge curve diagram of the solid-state battery assembled with the composite solid polymer electrolyte obtained in Example 1, LiFeO4 and metal lithium electrode at -10°C and 0.1C test conditions for the 21st to 25th cycles. DETAILED DESCRIPTION

[0035] In order to further understand the technical solution of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0036] The organic solvents used in the following examples were all analytically pure.

[0037] Embodiment 1:

[0038] (1) First, 1.000 g of lithium bis(trifluoromethylsulfonyl)imide (≥99.9%, Aladdin) was dissolved in 1.000 g of N,N-dimethylformamide (AR, 99.5%, Aladdin), and the mixture was stirred at 30° C. for 6 h to obtain a uniform solution A;

[0039] (2) Then 1.000 g of polyvinylidene fluoride (average M W ≈400000, Aladdin) and 1.000g solution A were dissolved in 20.000g acetonitrile (>99.5%, GC, Aladdin), and stirred for 6h at 50℃ to obtain a uniform solution B; the solution B was filled into a commercial PE polymer film (thickness 7μm, SK ENERGY Co., Ltd) by dip coating, and then placed at 40℃ for vacuum drying for 36h to obtain the target product composite polymer solid electrolyte. Its cross-sectional SEM image is shown in Figure 1 As shown, it can be observed that its thickness is about 12 μm, and the electrolyte is in a dense state. The solvents selected in this embodiment are N, N-dimethylformamide and acetonitrile. N, N-dimethylformamide can form a complex with lithium salt and be bound by the polymer inside the ultra-thin film. At the same time, a large amount of acetonitrile slowly evaporates during the drying process to avoid the formation of micropores in the electrolyte.

[0040] The mechanical properties of the obtained composite solid polymer electrolyte were tested. Figure 2 The stress-strain curve shows that the strength limit of the composite polymer solid electrolyte exceeds 140MPa, and the deformation reaches more than 140%. In addition, the prepared composite solid electrolyte was subjected to electrochemical impedance spectroscopy (EIS) test at room temperature (25°C, the same below) (with steel sheet as blocking electrode and test frequency of 10 to 10 6 Hz) and cyclic voltammetry (metal lithium as reference electrode, stainless steel as counter electrode, scan rate of 1 mV·s -1 ), the results show that its room temperature ionic conductivity is 1.12×10 -4 S cm -1 , the electrochemical stability window is close to 5.3 V, indicating that the obtained material has good ionic conductivity and electrochemical stability.

[0041] Figure 3This is a cycle performance diagram of a solid-state battery assembled with the composite solid polymer electrolyte obtained in Example 1, LiFeO4 and a metal lithium electrode at room temperature at 0.5C. The discharge capacity of the obtained solid-state battery after stabilization is 140.5 mAh·g -1 , the cycle retention rate after 600 cycles is close to 100%.

[0042] Figure 4 The cycle performance diagram of the all-solid-state battery assembled with the composite solid polymer electrolyte obtained in Example 1, LiFeO4 and metal lithium electrode at 0°C and 0.1C is shown. It can be seen that the solid-state battery can not only perform normal charge and discharge cycles at 0°C, but also maintain a high discharge specific capacity and capacity retention rate. After 100 cycles at 0.1C, it can still maintain 142.2 mAh·g -1 The discharge capacity.

[0043] Figure 5 This is a charge and discharge curve diagram of the solid-state battery assembled with the composite solid polymer electrolyte obtained in Example 1, LiFeO4 and metal lithium electrode at -10°C and 0.1C test conditions for the 21st to 25th cycles. It can be seen that the solid-state battery can work normally at -10°C and can cycle stably while maintaining a high discharge specific capacity.

[0044] Embodiment 2:

[0045] (1) First, 0.800 g of lithium tetrafluoroborate (99.99%, metal basis, Aladdin) was dissolved in 1.200 g of N-methylpyrrolidone (electronic grade, 99.9%, Aladdin), and the mixture was stirred at 50° C. for 4 h to obtain a uniform solution A;

[0046] (2) Then 1.000 g of polyethylene oxide (average M W ≈400000, Aladdin) and 1.000 g of solution A were simultaneously dissolved in 15.000 g of acetone (ACS, ≥99.5%, Aladdin), and stirred at 40 °C for 6 h to obtain a uniform solution B;

[0047] (3) The polyvinylidene fluoride and hexafluoropropylene copolymer (average M W≈400000, Aladdin) was dissolved in a certain volume of tetrahydrofuran (chromatographic grade, ≥99.9%, Aladdin), and an ultra-thin porous polymer film (the thickness of the porous polymer film was about 5-20 μm) was prepared by phase inversion method. By changing the thickness of the film applicator, porous polymer films with thicknesses of 7 μm and 20 μm were prepared respectively. Finally, solution B was filled into the interior of the ultra-thin porous polymer film by dip coating, and then placed at 50°C for vacuum drying for 24 hours to prepare composite polymer solid electrolytes with thicknesses of 12 μm and 24 μm respectively. SEM test found that the surfaces of the two composite solid polymer electrolytes were dense and had no micropores.

[0048] The mechanical properties of the composite polymer solid electrolyte were tested by an electronic tensile testing machine:

[0049] When the thickness of the composite solid polymer electrolyte is about 12 μm, its strength limit (tensile strength, the same below) exceeds 7.6 MPa, and the deformation (tensile strength, the same below) reaches 180%. In addition, the prepared composite electrolyte material was subjected to electrochemical impedance spectroscopy (EIS) test at room temperature (with steel sheet as blocking electrode and test frequency of 10 to 10 6 Hz) and cyclic voltammetry (metal lithium as reference electrode, stainless steel as counter electrode, scan rate of 1 mV·s -1 ), the results show that the room temperature ionic conductivity is 1.15×10 -4 S cm -1 The electrochemical stability window is close to 5.1V, indicating that the obtained material has good ionic conductivity and electrochemical stability. The solid-state battery assembled with the sample and LiFeO4 and metal lithium electrodes has a discharge capacity of 134.8mAh·g at 0.5C at room temperature. -1 , the coulombic efficiency is close to 100%. When the test temperature drops to -10℃, under 0.1C test conditions, the solid-state battery can also cycle stably while maintaining a high discharge specific capacity.

[0050] When the thickness of the composite solid polymer electrolyte is about 24 μm, its strength limit exceeds 20 MPa, and the deformation reaches more than 190%. In addition, the prepared composite electrolyte material is subjected to electrochemical impedance spectroscopy (EIS) test at room temperature (with steel sheet as blocking electrode and test frequency of 10 to 10 6 Hz) and cyclic voltammetry (metal lithium as reference electrode, stainless steel as counter electrode, scan rate of 1 mV·s -1 ), the results show that the room temperature ionic conductivity is 1.01×10 - 4 S cm -1The electrochemical stability window is close to 5.2V, indicating that the obtained material has good ionic conductivity and electrochemical stability. The solid-state battery assembled with the sample, LiFeO4 and metal lithium electrodes has a discharge capacity of 136.4mAh·g at 0.5C at room temperature. -1 , the coulombic efficiency is close to 100%. When the test temperature drops to -10℃, under 0.1C test conditions, the solid-state battery can also cycle stably while maintaining a high discharge specific capacity.

[0051] Embodiment 3:

[0052] (1) First, 2.000 g of lithium hexafluorophosphate (97%, Aladdin) was dissolved in 1.500 g of N-methylpyrrolidone (electronic grade, 99.9%, Aladdin), and the mixture was stirred at 30° C. for 2 h to obtain a uniform solution A;

[0053] (2) Then 1.000 g of polymethyl methacrylate (average M W ≈350000, Aladdin) and 2.000g of solution A were simultaneously dissolved in 20.000g of tetrahydrofuran (chromatographic grade, ≥99.9%, Aladdin), and stirred at 50°C for 5h to obtain a uniform solution B;

[0054] (3) Polytetrafluoroethylene (average particle size 200 μm, Aladdin) was dissolved in a certain volume of ethylene glycol (≥99%, GC, Aladdin), and was made into an ultrathin porous polymer membrane with a thickness of 15 μm by electrospinning. Finally, solution B was filled into the interior of the ultrathin porous polymer membrane by dip coating, and then it was placed at 50°C for vacuum drying for 36 hours to obtain the target product, a composite polymer solid electrolyte with a thickness of about 20 μm.

[0055] The mechanical properties of the composite polymer solid electrolyte were tested. The strength limit of the composite polymer electrolyte exceeded 10MPa, and the deformation reached more than 280%. In addition, the prepared composite solid electrolyte material was tested for electrochemical impedance spectroscopy (EIS) at room temperature (with steel sheets as blocking electrodes and a test frequency of 10 to 10 6 Hz) and cyclic voltammetry (metal lithium as reference electrode, stainless steel as counter electrode, scan rate of 1 mV·s -1 ), the results show that the room temperature ionic conductivity is 0.88×10 -4 S cm -1 The electrochemical stability window is close to 5.2V, indicating that the obtained material has good ionic conductivity and electrochemical stability. The solid-state battery assembled with the sample and LiFeO4 and metal lithium electrodes has a discharge capacity of 139.6mAh·g at 0.5C at room temperature. -1, the coulombic efficiency is close to 100%. When the test temperature drops to -10℃, under 0.1C test conditions, the solid-state battery can also cycle stably while maintaining a high discharge specific capacity.

[0056] Comparative Example:

[0057] (1) First, 1.000 g of lithium bis(trifluoromethylsulfonyl)imide (≥99.9%, Aladdin) was dissolved in 1.000 g of N,N-dimethylformamide (AR, 99.5%, Aladdin), and the mixture was stirred at 30° C. for 6 h to obtain a uniform solution A;

[0058] (2) Then 1.000 g of polyvinylidene fluoride (average M W ≈400000, Aladdin) and solution A were dissolved in 20.000 g of N,N-dimethylformamide, and stirred at 50 °C for 6 h to obtain a uniform solution B;

[0059] (3) The solution B was filled into a commercial PE polymer film (7 μm, SK ENERGY Co., Ltd) by dip coating, and then placed at 80°C for vacuum drying for 48 hours to obtain the target product, a composite polymer solid electrolyte with a thickness of 15 μm. Since the same non-volatile organic solvent was selected, the evaporation rate of the solvent was lower than the phase separation rate of the electrolyte during the subsequent drying process, which would lead to the formation of pores inside and on the surface of the electrolyte. This would affect the electrochemical stability of the electrolyte.

[0060] The mechanical properties of the composite polymer solid electrolyte were tested. The strength limit of the composite polymer solid electrolyte exceeded 110MPa, and the deformation reached more than 105%. In addition, the prepared composite polymer solid electrolyte material was subjected to electrochemical impedance spectroscopy (EIS) test at room temperature (25°C, the same below) (with steel sheet as blocking electrode and test frequency of 10 to 10 6 Hz) and cyclic voltammetry (metal lithium as reference electrode, stainless steel as counter electrode, scan rate of 1 mV·s -1 ), the results show that the room temperature ionic conductivity is 1.42×10 -4 S cm -1 , the electrochemical stability window is close to 4.5V. The improvement of the ionic conductivity of the composite polymer solid electrolyte is due to the presence of a solvent that is difficult to release inside the electrolyte, but this residual solvent directly affects the electrochemical stability of the electrolyte, resulting in a significantly reduced electrochemical stability window. The sample in Example 2 was assembled with LiFeO4 and a metal lithium electrode into a solid-state battery and charged and discharged at a rate of 0.5C at room temperature. The solid-state battery obtained after stabilization had a discharge capacity of 110.5mAh·g -1, the cycle stability is poor, and the capacity retention rate after 600 cycles is 65.5%. When the test temperature is adjusted to 0℃ and the current density is adjusted to 0.1C, the battery cannot be charged and discharged normally.

Claims

1. A method for preparing an ultra-thin composite polymer solid electrolyte suitable for low temperature operation, comprising the following steps: (1) adding lithium salt to an organic solvent M, stirring continuously for a certain period of time at a certain temperature to obtain a uniform solution A; (2) placing the solution A and polymer P in step (1) in an organic solvent N, controlling the temperature to a certain level, and continuously stirring for a certain period of time to obtain a uniform solution B; (3) filling the solution B in step (2) into the interior of the ultra-thin porous polymer membrane by dip coating, and then drying the membrane to obtain the target product, a composite polymer solid electrolyte; The organic solvent M is selected from one or more of toluene, xylene, cyclohexanone, N-methylpyrrolidone, ethylene glycol, N,N-dimethylformamide, N,N-dimethylacetamide, methyl acetate, ethyl acetate, ether, methanol, and benzyl alcohol; The organic solvent N is selected from one or more of tetrahydrofuran, butyl acetate, ethanol, propanol, isopropanol, n-butanol, isobutanol, acetone, methyl isobutyl ketone, methyl butyl ketone, dimethyl sulfoxide, and acetonitrile; Furthermore, the organic solvent M and the organic solvent N are different organic solvents.

2. The preparation method according to claim 1, characterized in that: The ultra-thin porous polymer membrane in step (3) is a commercial porous polymer membrane commonly available on the market or is prepared by the following method: The polymer Q is dissolved in a certain volume of organic solvent L, the temperature is controlled at a certain level, and stirring is continued for a certain period of time to obtain a uniform solution C, and then the solution C is made into an ultra-thin porous polymer film by coating, phase inversion or electrospinning.

3. The preparation method according to claim 1, characterized in that: The lithium salt described in step (1) is selected from one or more of lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonic acid)imide (LiN(CF3SO2)2), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium bis(fluorosulfonyl imide) (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluorooxalatophosphate (LiPF4(C2O4)), perfluoroalkyl lithium phosphate (LiPF3(C2F5)3), and lithium bis(oxalatoborate) (LiBOB).

4. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium salt to the organic solvent M is (0.01-5):1; and / or The mass ratio of the polymer P, the solution A and the organic solvent N is (0.01-5):1:(5-50); and / or The drying time in step (3) is 0.01 to 10 hours, and the drying temperature is 20 to 100°C.

5. The preparation method according to claim 1, characterized in that: The stirring temperature in step (1) is 20-100° C., and the stirring time is 1-12 h. The stirring temperature in step (2) is 20-80° C., and the stirring time is 1-12 h.

6. The preparation method according to claim 1, characterized in that: The polymer P described in step (2) is selected from one or more of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer, carboxymethyl cellulose, polyethylene glycol methyl ether acrylate, polyvinyl alcohol, polyvinyl alcohol ether, polystyrene, polytrimethylene carbonate, polyethylene carbonate, polyvinylene carbonate, polypropylene carbonate, polycyanoacrylate, and polypentaerythritol tetraacrylate.

7. The preparation method according to claim 2, characterized in that: The polymer Q is selected from one or more of polymethyl methacrylate, polytrifluoroethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polyurethane, polytetrafluoroethylene; and / or The organic solvent L is selected from one or more of tetrahydrofuran, methyl acetate, ethyl acetate, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, benzyl alcohol, ethylene glycol, and N-methylpyrrolidone, and is different from the organic solvent N; and / or The commercial porous polymer membrane is selected from one of polyethylene, polypropylene, polyurethane, polytetrafluoroethylene, polystyrene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene copolymer.

8. Use of the composite polymer solid electrolyte obtained by the preparation method according to any one of claims 1 to 7 in solid lithium secondary batteries.